2017
DOI: 10.1016/j.sleh.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between school start time, sleep duration, and adolescent behaviors

Abstract: Given that later start times allow for greater sleep duration and that adequate sleep duration is associated with more favorable mental health- and substance use-related issues and behaviors, it is important that school districts prioritize exploring and implementing policies, such as delayed start times, that may increase the amount of sleep of adolescent students, which is needed for their optimal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 31 publications
0
36
1
Order By: Relevance
“…In order to promote the health and well-being of adolescents, interventions to improve sleep duration are needed. There is strong evidence that delaying school start time can be the most effective method to benefi t adolescent sleep (32)(33)(34)(35)(36). The role of parental bedtime monitoring in relation to sleep duration is also hugely discussed in recent studies (13,15,24), therefore future research is needed to investigate this association in Slovak adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote the health and well-being of adolescents, interventions to improve sleep duration are needed. There is strong evidence that delaying school start time can be the most effective method to benefi t adolescent sleep (32)(33)(34)(35)(36). The role of parental bedtime monitoring in relation to sleep duration is also hugely discussed in recent studies (13,15,24), therefore future research is needed to investigate this association in Slovak adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between high school starting times, adolescent sleep duration, mental health and substance use related issues and behaviors were examined from the Teen Sleep Habits Survey in the United States. It was found that later starting times were significantly associated with greater sleep duration and greater sleep duration was associated with fewer reports of various mental health and substance use related issues and behaviors (Wahlstrom et al 2017). The effects of SST on sleep duration of students were examined in a metaanalysis which included five longitudinal studies and 15 cross-sectional comparison group studies.…”
Section: School Schedules Changesmentioning
confidence: 99%
“…Chronic sleep reduction can have detrimental effects on the lives of adolescents, with evidence linking it to decreased mental and physical alertness, increased feelings of anxiety, depression and hopelessness, poor academic performance, and obesity, among others (Dewald, Meijer, Oort, Kerkhof, & Bögels, 2010;Minges & Redeker, 2016;Paruthi et al, 2016;Perkinson-Gloor, Lemola, & Grob, 2013;Wahlstrom, Berger, & Widome, 2017).…”
Section: Introductionmentioning
confidence: 99%